New Korean cinema - Shin, Chi-Yun; Stringer, Julian, 1966- (Edinburgh University Press, 2005)
A wide-ranging analysis of one of the world's most important contemporary film industries, New Korean Cinema adopts a cross-cultural and multi-dimensional perspective and provides a comprehensive overview of the production, circulation and reception of modern South Korean cinema. Together with discussions of Korean society and culture, it considers the political economy of the film industry, strategies of domestic and international distribution and marketing, the consumption of films in diverse reception environments, and the relation of film texts to their cultural, historical and social contexts. Gathering critics from Asia, Europe and North America, New Korean Cinema contributes to the discussion of the complex role played by national and regional cinemas in a global age. It will be of interest to students and critics of Popular Culture and Film Studies as well as East Asian Studies and Korean Studies. Key Features The most comprehensive study of one of the world's most exciting new cinemas Provides new insights into the relations forged between cinema and civil society since the early 1990s. Considers innovative and timely areas of concern such as globalization, transnationalism and new media Contains in-depth analyses of key films like Chunhyang, Memento Mori, Peppermint Candy and Take Care of My Cat Includes a glossary of key terms and bibliography of works on Korean cinema Illustrated with 24 black-and-white stills.